A review on modified polymer composite electrolytes for solid-state lithium batteries. Issue 22 (20th October 2022) - Luo, Shengbin; Liu, Xia; Gao, Lu; Deng, Nanping; Sun, Xiaobin; Li, Yanan; Zeng, Qiang; Wang, Hao; Cheng, Bowen; Kang, Weimin
Abstract : High performance modified polymer composite electrolytes are obtained by compounding polymers with other substances. Abstract : Solid electrolytes are considered to be the key to improve the energy density and safety of lithium batteries. Currently, solid polymer electrolytes in various solid electrolytes have been considered as a promising solution, and hence solid polymer-based solid-state lithium batteries have attracted much attention due to their high safety when compared to their counterparts. However, polymer electrolytes have some problems at room temperature such as unsatisfactory ionic conductivity, low mechanical strength and the growth of lithium-dendrites and parasitic reactions. Composite electrolytes can be obtained by compounding polymers with other substances, and have excellent ionic conductivity and mechanical strength and good interfacial contact with electrodes. In this review, the application of modified polymer composite electrolytes with other fillers in solid-state lithium batteries is summarized. For composite electrolytes, the addition of fillers ( e.g., oxides, sulfides, halides, etc. ) can greatly improve the ionic conductivity, inhibit the serious growth of lithium dendrites, improve the mechanical strength of electrolytes, and enhance the heat resistance of electrolytes. Especially for the composite electrolyte compounded with oxides, the improvement of mechanical properties and the inhibition of lithium dendrites by zero-dimensional, one-dimensional, two-dimensional and three-dimensional materials, as well as the action mechanism of different fillers in the composite electrolyte are presented in detail. Finally, we conclude with the prospect section to provide some insights into the applications of oxides, sulfides, halides, nitrides and phosphates in different polymer electrolytes. These discussions and suggestions will present more valuable approaches for the practical application of modified polymer composite electrolytes with high electrochemical performance and safety in the future.